PENGEMBANGAN SISTEM MANAJEMEN PERAWATAN FORKLIFT DENGAN PENDEKATAN RELIABILITY CENTERED MAINTENANCE (RCM) BERBASIS ORACLE ALERT SYSTEM (Studi pada PT Gajah Tunggal Tbk Tangerang) - Susetyo Anggoro (Universitas Mercu Buana, 2014)
Abstract. In the production system, all machineries and support system has arole in supporting the achievement of production targets. To achieve thesegoals, each machine and its supporting assets, including forklifts, need to bemaintained. In large quantities controlling the maintenance system in manualway is not possible anymore. The current maintenance system in PT GajahTunggal still rely on manual control, where the system information formaintenance scheduling forklift still rely on telephone and the maintenanceitems are still very simple, even just oil changes. Apllying a modern systemmaintenance with RCM approach is posible and on its implementation,combined with the ERP system that has been applied to the productionmachinerries, the oracle system module EAM (Enterprise Asset Management)and take advantage of advanced features of the oracle alerts. Forkliftmaintenance schedule information is automatically sent to the owner of theforklift, which is spread in many areas, by means of e-mail has been setup on thecell-phone will minimizes the possibility of not getting or forgotten information.Keywords: maintenance system, information system, oracle alert